Preparation method of radiation cross-linked low-smoke flame-retardant polyolefin cable material
A radiation cross-linked polyolefin cable material with a specially synthesized flame retardant enhances flame retardancy and smoke suppression, addressing safety and efficiency issues in existing polyolefin cable materials.
Patent Information
- Application Number
- CN202411364417.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-29
AI Technical Summary
Existing polyolefin cable materials lack effective flame retardancy and generate excessive smoke when burning, posing safety risks due to the use of halogen-based flame retardants, and existing cross-linking methods are inefficient or environmentally harmful.
A method involving the preparation of a radiation cross-linked low-smoke flame-retardant polyolefin cable material using high-density polyethylene, ethylene-vinyl acetate copolymer, modified hydrotalcite, and a specially synthesized flame retardant containing DOPO, triazine, phenol, and long carbon chain structures, combined with a cross-linking sensitizer, to enhance flame retardancy and smoke suppression.
The cable material achieves stable and efficient flame retardancy, smoke suppression, and improved mechanical properties with reduced environmental impact, forming a tight network structure under irradiation.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cable materials, and in particular relates to a method for preparing a radiation cross-linked low-smoke flame-retardant polyolefin cable material. Background Art
[0002] Polyolefins are generally referred to as a class of thermoplastic resins obtained by polymerization or copolymerization of α-olefins such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 4-methyl-1-pentene, and some cyclic olefins. The English abbreviation is PO. Polyolefins have the characteristics of low relative density, good corrosion resistance, water resistance, and electrical insulation, and are widely used in the cable industry.
[0003] At present, although polyolefin cable materials occupy a large market share, with the advancement of science and technology, people's performance requirements for cables are also increasing. The most effective way to improve the performance of polyolefin materials is to use a cross-linking process to make cross-linked polyolefin materials. Commonly used cross-linking methods include radiation cross-linking, peroxide cross-linking, and silane cross-linking. Among them, the peroxide cross-linking method is complex and has low production efficiency; the silane cross-linking method involves a series of reactions of water, which requires investment in additional equipment to affect efficiency and has poor stability. Radiation cross-linking is a method of forming free radicals through the electron current emitted by radiation under the action of a sensitizer, initiating cross-linking. The degree of cross-linking is uniform and controllable. It is an efficient and environmentally friendly cross-linking method that is increasingly valued by the industry. However, as a high-molecular organic material, polyolefin has poor flame retardant properties and is very easy to burn when exposed to open flames, seriously endangering people's lives and property safety.
[0004] At present, flame retardants are often added to polyolefin cable materials to improve the flame retardant properties of polyolefin cable materials. However, the commonly used flame retardants on the market are still mainly halogen and halogen-antimony flame retardants. When these halogen flame retardant materials burn, they release a lot of smoke and toxic and harmful hydrogen halide gas. Since their diffusion speed is much faster than the flame diffusion speed, they are easy to hinder the rapid evacuation of personnel and fire fighting, causing serious impact and loss of people's lives and property safety. Therefore, it is urgent to invent a radiation cross-linked low-smoke flame retardant polyolefin cable material to meet the higher demands in the field of cable material technology. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a method for preparing a radiation cross-linked low-smoke flame-retardant polyolefin cable material.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing a radiation cross-linked low-smoke flame-retardant polyolefin cable material comprises the following steps:
[0008] High-density polyethylene, ethylene-vinyl acetate copolymer (EVA), modified hydrotalcite, flame retardant, cross-linking sensitizer and lubricant are put into a twin-screw extruder for melt blending, and irradiated with an electron accelerator after extrusion to obtain irradiation cross-linked low-smoke flame-retardant polyolefin cable material.
[0009] Furthermore, the flame retardant is prepared by the following steps:
[0010] S1. In a three-necked flask equipped with a stirring reflux device, melamine, salicylaldehyde, N,N-dimethylformamide (DMF) and piperidine (condensation agent) were stirred and mixed uniformly, and refluxed at 75°C for 4 hours. After the reaction was completed, the mixture was naturally cooled and filtered, washed with anhydrous ethanol, and vacuum dried to obtain intermediate 1; the ratio of melamine, salicylaldehyde, N,N-dimethylformamide and piperidine was 13.5g:24.4g:100mL:15mL;
[0011] Under the action of the condensing agent, the amino group on melamine condenses with the aldehyde group on salicylaldehyde to form an imine group (C=N Schiff base structure). By controlling the molar ratio of the two to be close to 1:2 and a slight excess of melamine, two amino groups on melamine participate in the reaction to obtain intermediate 1. The specific reaction process is as follows:
[0012] ;
[0013] S2. Under nitrogen protection, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), intermediate 1, azobisisobutyronitrile (AIBN) and methanol were stirred and mixed evenly in a three-necked flask equipped with a magnetic stirring reflux device, and the reaction temperature was controlled to 80°C. The reaction was refluxed for 10 hours. After the reaction was completed, the mixture was cooled to room temperature and filtered. The precipitate was washed by centrifugation with anhydrous ethanol and dried in vacuo to obtain intermediate 2. The ratio of DOPO, intermediate 1, AIBN and methanol was 43.2 g:34.1 g:0.4 g:200 mL.
[0014] Under the catalysis of AIBN, intermediate 1 reacts with DOPO, and intermediate 2 is obtained by controlling the molar ratio of the two to be close to 1:2. The specific reaction process is as follows:
[0015] ;
[0016] S3. In a three-necked flask equipped with a stirring device, the intermediate 2 and toluene were mixed and stirred evenly; nitrogen was introduced, 9-decenoic acid and dicyclohexylcarbodiimide (DCC, a dehydrating agent) were added and mixed and stirred evenly, and the mixture was placed in a water bath and kept warm at 50°C for 90 minutes. After the reaction was completed, the mixture was filtered, most of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of ethyl acetate / benzene, and the volume ratio of the two was 2:5), and the eluent was removed by rotary evaporation to obtain a flame retardant; the ratio of the amount of intermediate 2, toluene, 9-decenoic acid, and dicyclohexylcarbodiimide was 76.6 g: 200 mL: 16.9 g: 20.6 g;
[0017] The carboxyl group on 9-decenoic acid and the amino group of intermediate 2 undergo an amidation reaction. Under the action of a dehydrating agent, the reaction can be carried out under relatively mild conditions to obtain a flame retardant. The specific reaction process is as follows:
[0018] ;
[0019] The prepared flame retardant molecule contains DOPO flame retardant structure, triazine structure, phenol structure and long carbon chain structure, among which DOPO flame retardant structure is non-toxic, non-migrating and has long-lasting flame retardant performance. It can also promote the dehydration of the material surface into carbon elastomer, realize condensed phase flame retardancy, and give the matrix excellent flame retardant and smoke suppression performance. In addition, the DOPO structure is also a phosphophanate cyclic phosphate, which can give the matrix certain thermal stability and antioxidant properties. In addition, the introduced triazine structure will produce nitrogen-containing gas during combustion, dilute and reduce the smoke density, and self-condense at high temperature to form melem to make the carbon layer tight, which can play a synergistic role with DOPO and greatly enhance the flame retardant and smoke suppression performance of the matrix. In addition, the introduction of phenol structure has certain antioxidant properties, which can not only improve the antioxidant property of the matrix, but also act as an antioxidant in the refining process, avoiding the addition of additional antioxidants to affect the homogeneity of the matrix. Finally, the introduced long carbon chain is a methylene chain segment, which can be interspersed in the cross-linked structure of the matrix, which not only improves the mechanical properties of the matrix, but also improves the stability of the flame retardant.
[0020] It should be noted that the flame retardant molecules also contain carbon-carbon double bonds. Under the action of the cross-linking sensitizer, they can cross-link with the matrix during the irradiation process, thereby improving the flame retardant's resistance to migration and exudation, making the performance of the flame retardant long-term and stable.
[0021] Furthermore, the modified hydrotalcite is prepared by the following steps:
[0022] In a three-necked flask, magnesium aluminum hydrotalcite was mixed with deionized water. After vigorous stirring for 30 minutes, boric acid and sodium dodecylbenzene sulfonate were added in sequence, and dilute nitric acid (mass fraction 24%) was added dropwise to adjust the pH of the system to 4. The device was placed in a 70°C water bath and stirred for 3 hours. After the reaction was completed, it was cooled and allowed to stand for 24 hours. The supernatant was poured out, the bottom liquid was filtered with filter paper, and then washed with deionized water and anhydrous ethanol until the filtrate was neutral. The filter cake was dried at 60°C overnight, ground, and passed through a 200-mesh sieve to obtain the modified hydrotalcite.
[0023] Furthermore, the usage ratio of magnesium aluminum hydrotalcite, deionized water, boric acid and sodium dodecylbenzene sulfonate is 1 g:100 mL:2.5 g:3 g.
[0024] Magnesium aluminum hydrotalcite has the advantages of both magnesium hydroxide and aluminum hydroxide flame retardants, and has the advantages of being non-toxic, low smoke, easy to prepare, and low-priced. It absorbs a large amount of heat when decomposed at high temperatures, and also releases a large amount of H2O and CO2. It has excellent flame retardancy and smoke suppression. Boric acid and sodium dodecylbenzene sulfonate are used as modifiers, and the modified hydrotalcite is prepared by ion exchange method, which can greatly reduce the hydrophilicity of the hydrotalcite and improve its hydrophobic properties, thereby enhancing the compatibility of the modified hydrotalcite with the polyolefin matrix, promoting the dispersion of the hydrotalcite in the matrix, and enhancing the flame retardant efficiency.
[0025] Furthermore, the raw materials are calculated in parts by weight as follows: 60-80 parts of high-density polyethylene, 20-30 parts of ethylene-vinyl acetate copolymer, 10-20 parts of modified hydrotalcite, 5-15 parts of flame retardant, 4-8 parts of cross-linking sensitizer, and 2-4 parts of lubricant.
[0026] Furthermore, the cross-linking sensitizer is one of triallyl cyanurate, triallyl isocyanurate and trimethylolpropane trimethacrylate.
[0027] Furthermore, the lubricant is one of paraffin and stearamide fatty acid.
[0028] High-density polyethylene is used as the main matrix, which gives the cable material good heat resistance, mechanical and insulation properties; the addition of ethylene-vinyl acetate copolymer enhances the aging resistance of the cable material; the cross-linking sensitizer used is a multifunctional cross-linking sensitizer, which has good compatibility with the matrix and can promote the cross-linking of the polymer chains of the matrix under irradiation to form a tight network structure, greatly improving the comprehensive performance of the cable material.
[0029] Beneficial effects of the present invention:
[0030] 1. The cable material prepared by the present invention uses high-density polyethylene as the main matrix and adds ethylene-vinyl acetate copolymer, which gives the cable material good aging resistance, mechanical properties and insulation properties;
[0031] 2. The cross-linking sensitizer used is a multifunctional cross-linking sensitizer, which has good compatibility with the matrix. Under irradiation, it can promote the cross-linking of the polymer chains of the matrix to form a tight network structure, which greatly improves the comprehensive performance of the cable material. Compared with chemical cross-linking, it has high efficiency, low energy consumption and no pollution;
[0032] 3. Magnesium aluminum hydrotalcite is non-toxic, low-smoke and flame-retardant. By modifying magnesium aluminum hydrotalcite, it has better compatibility with the matrix than ordinary hydrotalcite, promotes the dispersion of hydrotalcite in the matrix, enhances the flame retardant efficiency, and improves the flame retardant and smoke suppression performance of cable materials;
[0033] 4. The various groups in the flame retardant molecules play a synergistic role, greatly enhancing the flame retardancy, smoke suppression, oxidation resistance and mechanical properties of the cable material to a certain extent, and the performance is long-lasting and stable;
[0034] Therefore, the cable material prepared by the present invention has stable and efficient flame retardancy, smoke suppression, and antioxidant properties, as well as high mechanical strength and excellent comprehensive performance, and has important application value in the field of cable material technology. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] Preparation of flame retardant:
[0038] S1. In a three-necked flask equipped with a stirring reflux device, 13.5 g of melamine, 24.4 g of salicylaldehyde, 100 mL of N,N-dimethylformamide and 15 mL of piperidine were stirred and mixed uniformly, and refluxed at 75° C. for 4 h. After the reaction was completed, the mixture was naturally cooled and filtered, washed with anhydrous ethanol, and vacuum dried to obtain intermediate 1;
[0039] S2. Under nitrogen protection, 43.2 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 34.1 g of intermediate 1, 0.4 g of azobisisobutyronitrile and 200 mL of methanol were stirred and mixed evenly in a three-necked flask equipped with a magnetic stirring reflux device. The reaction temperature was controlled to 80 ° C. The reflux reaction was carried out for 10 hours. After the reaction was completed, the mixture was cooled to room temperature and filtered. The precipitate was washed by centrifugation with anhydrous ethanol and dried in vacuo to obtain intermediate 2.
[0040] S3. In a three-necked flask equipped with a stirring device, 76.6 g of intermediate 2 and 200 mL of toluene were mixed and stirred evenly; nitrogen was introduced, 16.9 g of 9-decenoic acid and 20.6 g of dicyclohexylcarbodiimide were added and mixed and stirred evenly, the mixture was placed in a water bath, and the mixture was kept warm at 50°C for 90 min. After the reaction was completed, the mixture was filtered, most of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of ethyl acetate / benzene in a volume ratio of 2:5), the eluent was removed by rotary evaporation, and a flame retardant was obtained.
[0041] Example 2
[0042] Preparation of flame retardant:
[0043] S1. In a three-necked flask equipped with a stirring reflux device, 27.0 g of melamine, 48.8 g of salicylaldehyde, 200 mL of N,N-dimethylformamide and 30 mL of piperidine were stirred and mixed uniformly, and refluxed at 75° C. for 4 h. After the reaction was completed, the mixture was naturally cooled and filtered, washed with anhydrous ethanol, and vacuum dried to obtain intermediate 1;
[0044] S2. Under nitrogen protection, 86.4 g 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 68.2 g intermediate 1, 0.8 g azobisisobutyronitrile and 400 mL methanol were stirred and mixed evenly in a three-necked flask equipped with a magnetic stirring reflux device, the reaction temperature was controlled to 80 ° C, refluxed for 10 h, the reaction was completed, cooled to room temperature and filtered, the precipitate was washed by centrifugation with anhydrous ethanol, and vacuum dried to obtain intermediate 2;
[0045] S3. In a three-necked flask equipped with a stirring device, 153.2 g of intermediate 2 and 400 mL of toluene were mixed and stirred evenly; nitrogen was introduced, 33.8 g of 9-decenoic acid and 41.2 g of dicyclohexylcarbodiimide were added and mixed and stirred evenly, the mixture was placed in a water bath, and the mixture was kept warm at 50°C for 90 min. After the reaction was completed, the mixture was filtered, most of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of ethyl acetate / benzene in a volume ratio of 2:5), the eluent was removed by rotary evaporation, and a flame retardant was obtained.
[0046] Example 3
[0047] Preparation of modified hydrotalcite:
[0048] In a three-necked flask, 1 g of magnesium aluminum hydrotalcite was mixed with 100 mL of deionized water. After vigorous stirring for 30 min, 2.5 g of boric acid and 3 g of sodium dodecylbenzene sulfonate were added in sequence, and dilute nitric acid (mass fraction 24%) was added dropwise to adjust the pH of the system to 4. The device was placed in a 70°C water bath and stirred for 3 h. After the reaction was completed, it was cooled and allowed to stand for 24 h. The supernatant was poured out, the bottom liquid was filtered with filter paper, and then washed with deionized water and anhydrous ethanol until the filtrate was neutral. The filter cake was dried at 60°C overnight, ground, and passed through a 200-mesh sieve to obtain the modified hydrotalcite.
[0049] Example 4
[0050] Preparation of modified hydrotalcite:
[0051] In a three-necked flask, 2 g of magnesium aluminum hydrotalcite was mixed with 200 mL of deionized water. After vigorous stirring for 30 min, 5 g of boric acid and 6 g of sodium dodecylbenzene sulfonate were added in sequence, and dilute nitric acid (mass fraction 24%) was added dropwise to adjust the pH of the system to 4. The device was placed in a 70 ° C water bath and stirred for 3 h. After the reaction was completed, it was cooled and allowed to stand for 24 h. The supernatant was poured out, the bottom liquid was filtered with filter paper, and then washed with deionized water and anhydrous ethanol until the filtrate was neutral. The filter cake was dried at 60 ° C overnight, ground, and passed through a 200-mesh sieve to obtain the modified hydrotalcite.
[0052] Example 5
[0053] 60g of high-density polyethylene, 20g of ethylene-vinyl acetate copolymer (vinyl acetate content is 25%), 10g of the modified hydrotalcite prepared in Example 3, 5g of the flame retardant prepared in Example 1, 4g of triallyl cyanurate and 2g of paraffin are put into a twin-screw extruder, melt-blended, and irradiated with an electron accelerator after extrusion to obtain an irradiation cross-linked low-smoke flame-retardant polyolefin cable material;
[0054] The irradiation was performed using a domestically produced GJ-1.5 high-frequency and high-voltage electron accelerator with an energy of 1.5 MeV and a current of 20 mA; the irradiation dose rate was 4 kGy / time, and the total irradiation dose was 150 kGy.
[0055] Example 6
[0056] 70g of high-density polyethylene, 25g of ethylene-vinyl acetate copolymer (vinyl acetate content is 25%), 15g of the modified hydrotalcite prepared in Example 3, 10g of the flame retardant prepared in Example 1, 6g of triallyl isocyanurate and 3g of stearamide fatty acid are put into a twin-screw extruder, melt-blended, and irradiated using an electron accelerator after extrusion to obtain an irradiation cross-linked low-smoke flame-retardant polyolefin cable material;
[0057] The irradiation was performed using a domestically produced GJ-1.5 high-frequency and high-voltage electron accelerator with an energy of 1.5 MeV and a current of 20 mA; the irradiation dose rate was 4 kGy / time, and the total irradiation dose was 150 kGy.
[0058] Example 7
[0059] 80g of high-density polyethylene, 30g of ethylene-vinyl acetate copolymer (vinyl acetate content is 25%), 20g of the modified hydrotalcite prepared in Example 3, 15g of the flame retardant prepared in Example 1, 8g of triallyl isocyanurate and 4g of stearamide fatty acid are put into a twin-screw extruder, melt-blended, and irradiated using an electron accelerator after extrusion to obtain an irradiation cross-linked low-smoke flame-retardant polyolefin cable material;
[0060] The irradiation was performed using a domestically produced GJ-1.5 high-frequency and high-voltage electron accelerator with an energy of 1.5 MeV and a current of 20 mA; the irradiation dose rate was 4 kGy / time, and the total irradiation dose was 150 kGy.
[0061] Comparative Example 1
[0062] The flame retardant in Example 7 was replaced by a commercially available phosphorus-based flame retardant of equal mass, and the remaining steps were the same as those in Example 7 to prepare a cable material.
[0063] Comparative Example 2
[0064] Ordinary magnesium aluminum hydrotalcite of the same mass was used to replace the modified hydrotalcite in Example 7, and the remaining steps were the same as in Example 7 to prepare a cable material.
[0065] Comparative Example 3
[0066] Use commercially available radiation cross-linked low-smoke flame-retardant cable materials.
[0067] The cable materials of Examples 5-7 and Comparative Examples 1-3 were made into corresponding shapes according to different test standards, and the following performance tests were performed:
[0068] The tensile strength was determined using the national standard GB / T 1040-2006 "Determination of tensile properties of plastics";
[0069] The impact resistance is measured using the national standard GB / T 1043.1-2008 "Determination of impact properties of simply supported plastic beams Part 1: Non-instrumented impact test";
[0070] The induction time of the sample was determined using the national standard GB / T 19466.6-2009 "Plastics Differential Scanning Calorimetry (DSC) Part 6: Determination of Oxidation Induction Time (Isothermal OIT) and Oxidation Induction Temperature (Dynamic OIT)";
[0071] The national standard GB / T 2406-2008 "Test method for combustion performance of plastics" is used to measure the limiting oxygen index of the sample before and after being placed at room temperature for 180 days;
[0072] The national standard GB / T 8323.2-2008 "Plastic Smoke Generation Part 2: Single Chamber Test Method for Determining Smoke Density" was used to measure the smoke density of the sample before and after being placed at room temperature for 180 days;
[0073] The measured results are shown in the following table:
[0074] ;
[0075] It can be seen from the above table that the cable material prepared in the embodiment of the present invention has stable and efficient flame retardancy, smoke suppression, and antioxidant properties, as well as high mechanical strength and excellent comprehensive performance, and has important application value in the field of cable material technology.
[0076] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0077] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing irradiation cross-linked low-smoke flame-retardant polyolefin cable material, It is characterized in that The following steps are involved: High-density polyethylene, ethylene-vinyl acetate copolymer, modified hydrotalcite, flame retardant, cross-linking sensitizer and lubricant are put into a twin-screw extruder, melt-blended, extruded and irradiated to obtain irradiation cross-linked low-smoke flame-retardant polyolefin cable material; Wherein, the flame retardant is prepared by the following steps: S1. Mix melamine, salicylaldehyde, N,N-dimethylformamide and piperidine and stir them evenly. React them at 75°C for 4 hours. After the reaction, cool and filter them with suction, wash and dry them to obtain intermediate 1. The ratio of melamine, salicylaldehyde, N,N-dimethylformamide and piperidine is 13.5g:24.4g:100mL:15mL. S2. Under nitrogen protection, DOPO, intermediate 1, AIBN and methanol were stirred and mixed evenly, and refluxed at 80°C for 10 hours. After the reaction was completed, the mixture was cooled to room temperature and filtered, and the precipitate was washed by centrifugation and dried to obtain intermediate 2. The ratio of DOPO, intermediate 1, AIBN and methanol was 43.2 g: 34.1 g: 0.4 g: 200 mL. S3, the intermediate 2 and toluene are mixed and stirred evenly; nitrogen is introduced, 9-decenoic acid and dicyclohexylcarbodiimide are added, mixed and stirred evenly, and the mixture is kept at 50°C for 90 minutes. After the reaction is completed, the mixture is filtered, rotary evaporated, purified by column chromatography, and rotary evaporated to obtain a flame retardant; the ratio of the intermediate 2, toluene, 9-decenoic acid, and dicyclohexylcarbodiimide is 76.6g:200mL:16.9g:20.6g; Wherein, the modified hydrotalcite is prepared by the following steps: The magnesium aluminum hydrotalcite is mixed with deionized water, stirred, and then boric acid and sodium dodecylbenzene sulfonate are added in sequence, and then dilute nitric acid is added dropwise to adjust the pH of the system to 4, and the device is placed in a water bath and stirred. After the reaction is completed, the device is cooled and allowed to stand, and the supernatant is poured out. The bottom liquid is filtered with filter paper, and then washed until the filtrate is neutral. The filter cake is dried, ground, and sieved to obtain the modified hydrotalcite; Wherein, the cross-linking sensitizer is one of triallyl cyanurate, triallyl isocyanurate and trimethylolpropane trimethacrylate.
2. The method for preparing the radiation cross-linked low-smoke flame-retardant polyolefin cable material according to claim 1, It is characterized in that The raw materials are calculated in parts by weight as follows: 60-80 parts of high-density polyethylene, 20-30 parts of ethylene-vinyl acetate copolymer, 10-20 parts of modified hydrotalcite, 5-15 parts of flame retardant, 4-8 parts of cross-linking sensitizer, and 2-4 parts of lubricant.
3. The method for preparing the radiation cross-linked low-smoke flame-retardant polyolefin cable material according to claim 1, It is characterized in that The usage ratio of magnesium aluminum hydrotalcite, deionized water, boric acid and sodium dodecylbenzene sulfonate is 1g:100mL:2.5g:3g.
